Developmental Dysfunction of the Central Nervous System Lymphatics Modulates the Adaptive Neuro-Immune Response in the Perilesional Cortex in a Mouse Model of Traumatic Brain Injury - Wojciechowski, Sara; Virenque, Anaïs; Vihma, Maria; Galbardi, Barbara; Rooney, Erin Jane; Keuters, Meike Hedwig; Antila, Salli; Koistinaho, Jari; Noe, Francesco M. (Frontiers in Immunology, 2021)
Rationale: The recently discovered meningeal lymphatic vessels (mLVs) have been proposed to be 32 the missing link between the immune and the central nervous systems. The role of mLVs in 33 modulating the neuro-immune response following a traumatic brain injury (TBI), however, has not 34 been analyzed. Parenchymal T lymphocyte infiltration has been previously reported as part of 35 secondary events after TBI, suggestive of an adaptive neuro-immune response. The phenotype of 36 these cells has remained mostly uncharacterized. In this study, we identified subpopulations of T cells 37 infiltrating the perilesional areas 30 days post-injury (an early-chronic time point). Furthermore, we 38 analyzed how the lack of mLVs affects the magnitude and the type of T cell response in the brain 39 after TBI. Methods: TBI was induced in K14-VEGFR3-Ig transgenic (TG) mice or in their littermate 40 controls (WT; wild type), applying a controlled cortical impact (CCI). One month after TBI, T cells 41 were isolated from cortical areas ipsilateral or contralateral to the trauma and from the spleen, then 42 characterized by flow cytometry. Lesion size in each animal was evaluated by MRI. Results: In both 43 WT and TG-CCI mice, we found a prominent T cell infiltration in the brain confined to the 44 perilesional cortex and hippocampus. The majority of infiltrating T cells were cytotoxic CD8+ 45 expressing a CD44hiCD69+ phenotype, suggesting that these are effector resident memory T cells. 46 K14-VEGFR3-Ig mice showed a significant reduction of infiltrating CD4+ T lymphocytes, 47 suggesting that mLVs could be involved in establishing a proper neuro-immune response. Extension 48 of the lesion (measured as lesion volume from MRI) did not differ between the genotypes. Finally, 49 TBI did not relate to alterations in peripheral circulating T cells, as assessed one month after injury. 50 Conclusions: Our results are consistent with the hypothesis that mLVs are involved in the neuro- 51 immune response after TBI. We also defined the resident memory CD8+ T cells as one of the main 52 population activated within the brain after a traumatic injury.